Blood macro and microelements in dairy herds under grazing at the Institute of Animal Science. Technical note - Valera, Moises; Guti?rrez, Odilia; Gallego, Carlos; Oramas, Abel; S?nchez, Liyen (Cuban Journal of Agricultural Science, 2011)
Sixty grazing cows were sampled to make a study on the mineral status of dairy herds at the Institute of Animal Science. They were given protein supplement, according to production and physiological status. Twelve animals were randomly selected from each of the five units at the Institute. The same number of blood samples was collected, separating the serum and determining the concentrations of macroelements (Ca, Mg, K, and Na) and trace elements (Cu, Zn, and Fe). The average concentrations of each of the elements were in the physiological ranges established as normal for this animal species and category. Nevertheless, there were slight deficiencies in serum concentrations of K (3.65 and 3.73 mMol/L) and Cu (8.63 y 8.99 ?Mol/L). Key words: macroelements and microelements, trace elements, dairy herds, grazing, serum concentration.